Status Study of Tribal Handicraft-An option for livelihood of Tribal Community in the States of Arunanchal Pradesh Rajasthan, Uttaranchal and Chhattisgarh - Planning Commission (Planning Commission, 2006)
India has the largest concentration of tribal population in the world. The tribal are the children of nature and their lifestyle is conditioned by the eco-system. India due to its diverse ecosystems has a wide variety of tribal population. Tribes people constitute 8.14% of the total population of the country, numbering 84.51 million (2001 Census). There are 697 tribes notified by the Central Government under Article 342 of the Indian Constitution with certain tribes being notified in more than one State. More than half the Scheduled Tribe population is concentrated in the States of Madhya Pradesh, Chattisgarh, Maharashtra, Orissa, Jharkhand and Gujarat whereas in Haryana, Punjab, Delhi, Pondicherry and Chandigarh no community has been notified as a Scheduled Tribe.
Socio - Economic and Educational Development Society (SEEDS)
Government of India Planning Commission
Keywords: Tribal Handicraft Sector; People and Handicraft in Study Area; Status of handicraft in Study Area; economics of Handicraft in Study area; Arunachal Pradesh; Rajasthan; Chhattisgarh; Uttaranchal; Tribal Handicraft Economy; Government Initiatives